Right insular damage decreases heartbeat awareness and alters cardio-visual effects on bodily self-consciousness. (April 2015) - Ronchi, Roberta; Bello-Ruiz, Javier; Lukowska, Marta; Herbelin, Bruno; Cabrilo, Ivan; Schaller, Karl; Blanke, Olaf
Abstract: Recent evidence suggests that multisensory integration of bodily signals involving exteroceptive and interoceptive information modulates bodily aspects of self-consciousness such as self-identification and self-location. In the so-called Full Body Illusion subjects watch a virtual body being stroked while they perceive tactile stimulation on their own body inducing illusory self-identification with the virtual body and a change in self-location towards the virtual body. In a related illusion, it has recently been shown that similar changes in self-identification and self-location can be observed when an interoceptive signal is used in association with visual stimulation of the virtual body (i.e., participants observe a virtual body illuminated in synchrony with their heartbeat). Although brain imaging and neuropsychological evidence suggest that the insular cortex is a core region for interoceptive processing (such as cardiac perception and awareness) as well as for self-consciousness, it is currently not known whether the insula mediates cardio-visual modulation of self-consciousness. Here we tested the involvement of insular cortex in heartbeat awareness and cardio-visual manipulation of bodily self-consciousness in a patient before and after resection of a selective right neoplastic insular lesion. Cardio-visual stimulation induced an abnormally enhanced state of bodily self-consciousness; in addition, cardio-visual manipulation was associated with an experienced loss of the spatial unity of the self (illusory bi-location and duplication of his body), not observed in healthy subjects. Heartbeat awareness was found to decrease after insular resection. Based on these data we propose that the insula mediates interoceptive awareness as well as cardio-visual effects on bodily self-consciousness and that insular processing of interoceptive signals is an important mechanism for the experienced unity of the self. Highlights: Cardio-visual stimulation affects self-consciousness after right insular lesion. Illusory feeling of bi-location is elicited by synchronous cardio-visual stimulation. Reduced interoceptive awareness is caused by insular resection.